Dominant males exploit the courtship effort of subordinate males in an Amazonian fish - Pires, Tiago Henrique de Silva; Pinto, Kalebe da Silva; Borghezan, Elio de Almeida; Zuanon, Jansen Alfredo Sampaio (Animal Behaviour, 2021)
Reproductive behaviour is often targeted by behavioural parasitism due to its high energy costs and direct relationship with fitness. Courtship behaviour represents a substantial amount of the investment in reproduction, as it usually requires conspicuous movements that are energetically demanding and increase predation risk. Here, we present an alternative reproductive tactic in which dominant male sailfin tetra, Crenuchus spilurus Günther 1863, parasitize the courtship behaviour of subordinate males. By conducting field observations and controlled experiments in laboratory, we show that, under low availability of nesting sites, dominant males favour a close-range defence of nesting sites, while subordinate males invest more in courtship activities. However, subordinate males often directed courtship movements towards a nesting site dominated by a concealed dominant male, who subsequently took over the female and resumed courtship. Our laboratory experiment also showed that only dominant males obtained spawning success regardless of the amount of effort allocated to courtship behaviour, circumventing the initial female preference for the subordinate male. Subordinate males were more likely to initiate contests and ceased courtship upon losing aggressive contests. In such instances, the courtship effort of dominant males was higher, suggesting that dominant males modulate their courtship effort according to the effort of subordinate males. We refer to this tactic as courtship piracy. For being dependent on resource defence, the effectiveness of courtship piracy is contingent on the defendability of nesting sites. In a follow-up experiment, we show that dominant males invest more in nesting site defence only when nesting sites are scarce. Since rainfall controls the amount of nesting sites in the natural habitat, we suggest that seasonality modulates the relative contribution of courtship piracy and female mate choice to reproductive success. © 2021 The Association for the Study of Animal Behaviour
Keywords: Crenuchus spilurus